Study Of Feasibility Analysis Of Electricity Network On Water Pumps In Pamsimas Tambibendo Village - Huda, Fredyanto Koirul (Universitas Panca Marga, 2023)
This text discusses the importance of the electricity network in daily life, highlighting its uses in various activities such as lighting, cooking, and irrigation. It emphasizes the need to follow the standards of PUIL in installing the electricity network, particularly when operating water pumping equipment. The feasibility of the electrical network is crucial, with voltage drop being a major concern. Factors that can affect voltage drop include length, cross -sectional area, material type, load, and current. The research conducted utilizes quantitative research methods to collect and analyze data on the feasibility of the electrical network. The data, collected multiple times under different conditions, is analyzed to determine the percentage of voltage drop, with PUIL guidelines stating it should not exceed 5%. The study also compares measurements and calculations, revealing an average voltage drop percentage of 7.1% and an average voltage value of 15.7V, calculated from an initial voltage of 220V. The study concludes that the results are not feasible due to the high voltage drop percentage and a slight difference between measurements and calculations.